2000
DOI: 10.1089/rej.1.2000.3.37
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Phagocytic Function and Humoral Immune Response with Reference to Ascorbate Supplementation in Aging Humans

Abstract: Age-associated deficiency of vitamin C contributes to the impaired humoral immune response, which in turn plays a role in the increased risk of illness in old age. Healthy volunteers were given vitamin C supplementation. Neutrophil phagocytic function, complement C3 concen¬ tration, and immunoglobulin status were measured at 30, 60, and 90 days. Neutrophil phago¬ cytic function and levels of serum IgG and IgM and leukocytic ascorbate were considerably lower in the aged humans, but these decreases were attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Interestingly, multiple studies showed that the effect of vitamin C on phagocytic function of neutrophil is dose dependent. Vitamin C supplement in a dose of 200 mg to 1 g daily for 1–4 months improved neutrophilic phagocytic activity [ 43 , 44 ]. However, administration of 2 g of vitamin C on a daily basis for 2 weeks impaired bacterial killing activity of neutrophil [ 45 ].…”
Section: Immunomodulatory Effect Of Vitamin Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, multiple studies showed that the effect of vitamin C on phagocytic function of neutrophil is dose dependent. Vitamin C supplement in a dose of 200 mg to 1 g daily for 1–4 months improved neutrophilic phagocytic activity [ 43 , 44 ]. However, administration of 2 g of vitamin C on a daily basis for 2 weeks impaired bacterial killing activity of neutrophil [ 45 ].…”
Section: Immunomodulatory Effect Of Vitamin Cmentioning
confidence: 99%
“…Multiple studies showed that experimentally induced vitamin C deficiency leads to impaired cellular and humoral immune response [ 47 ]. Age-related vitamin C deficiency is associated with low IgG and IgM serum levels [ 43 ]. Evidence showed that vitamin C enhances proliferation, differentiation and maturation of T lymphocytes in vitro [ 48 , 49 ].…”
Section: Immunomodulatory Effect Of Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular concentrations of vitamin C in human leukocytes have been shown to decline with increasing age, accompanied by neutrophil function impairment. Oral administration of vitamin C resulted in improved neutrophil functions and serum immunoglobulin levels [40] . An earlier investigation showed that administration of 1 g of vitamin C together with 200 mg of vitamin E for 16 weeks to healthy elderly women enhanced neutrophil chemotaxis and phagocytosis, and decreased concentrations in serum lipid peroxides, which is indicative of improved resistance to oxidative stress [41] .…”
Section: Vitamin C and The Immune Systemmentioning
confidence: 99%
“…4 Our recent studies show that supplementation with ascorbic acid improves neutrophil phagocytic function, humoral immunity, and antioxidants in aging humans. 5,6 Compounds able to restore reduced glutathione are of therapeutic interest to ensure the antioxidative function of glutathione within the cell. One such antioxidant is lipoate, which is an essential cofactor in several mitochondrial dehydrogenase complexes.…”
Section: Introductionmentioning
confidence: 99%